Impact of galactooligosaccharides delivered in ovo on mitigating negative effects of heat stress on performance and welfare of broilers - A. Slawinska; M. Zampiga; F. Sirri; A. Meluzzi; M. Bertocchi; S. Tavaniello; G. Maiorano (Poultry Science, 2020)
ABSTRACT: Galactooligosaccharides (GOS) delivered in ovo improve intestinal health of broiler chickens. This study aimed to demonstrate the impact of in ovo stimulation with GOS prebiotic on day 12 of egg incubation on performance and welfare traits in broiler chickens. The incubating eggs were divided into 3 groups, based on the substance injected in ovo: 3.5 mg of GOS dissolved in 0.2 mL physiological saline (GOS), 0.2 mL physiological saline (S), or uninjected controls (C). Constant heat stress (HS) was induced on days 32 to 42 post-hatch by increasing environmental temperature to 30°C. Thermoneutral (TN) animals were kept at 25°C. The performance (body weight [BW], daily feed intake [DFI], daily weight gain [DWG], and feed conversion rate [FCR]) were measured and mortality was scored for starter (days 0 to 13), grower (days 14 to 27), and finisher (days 28 to 42) feeding phases. Rectal temperature was scored on days 32 to 42. Food-pad dermatitis (FPD) was scored post-mortem (day 42). GOS increased (P < 0.01) BW on day 42 (2.892 kg in GOS vs. 2.758 kg in C). Heat stress significantly reduced (P < 0.01) final BW (2.516 kg in TN vs. 3.110 kg in HS). During finisher phase, DFI was significantly higher in GOS vs. C (173.2 g vs. 165.7 g; P < 0.05). FCR calculated for the entire rearing period (days 0 to 42) ranged from 1.701 in C to 1.653 in GOS (P < 0.05). GOS improved FCR in HS animals during finisher phase (P < 0.05). Rectal temperature of GOS chickens under HS reached 42.5°C 1 day earlier than C and S (P < 0.05), which suggests that those birds recovered earlier from the high environmental temperature. Heat stress increased (P < 0.05) mortality about 5 times compared to TN during finisher phase (from 1.59% in TN to 7.69% in HS). GOS decreased FPD in TN conditions by 20% (no lesions in 81% in GOS vs. 60% in C). GOS delivered in ovo mitigated negative effects of HS on performance and welfare in broiler chickens.